MOTIVASI, KOMUNIKASI, DAN LINGKUNGAN KERJA BERPENGARUH TERHADAP SEMANGAT KERJA GURU DI SMP NEGERI 5 DENPASAR - Pratiwi, Ni Made Ariesta Yuna; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen; Vol 9 No 7 (2020)DO - 10.24843/EJMUNUD.2020.v09.i07.p01, 2020)
Work morale is the mental attitude of individuals and groups that are able to create  work atmosphere, encourage cooperation, and can complete tasks on time. To increase morale, it is necessary to pay attention to the factors that influence it. The purpose of this study was to determine the effect of motivation, communication, and work environment on work morale. This research was conducted at SMP Negeri 5 Denpasar. 56 teachers are used as sampleswith saturated sampling method. Data collection collected by interviews and questionnaires. The analysis technique used is multiple linear regression. Motivation, communication, and work environment have positive and significant effect on teacher morale. SMP Negeri 5 Denpasar is expected to further improve health care, pay attention to the communication of fellow teachers, and arrange the room so that teachers feel comfortable in working. Keywords: motivation, communication, work environment, work morale